The Analysis of Fishermen's Fishing Income Business and Factors Affecting in Medan Belawan District - Amalia*, Amalia; Lubis, Irsad; Sukardi, Sukardi; Ruslan, Dede; Tanjung, Ahmad Albar; Sari, Rania Linda (Universitas Syiah Kuala, 2023)
The objective of the research done in the subdistrict of Medan Belawan is to quantify the extent of the disparity in fishermen's catch business revenue and examine the elements that contribute to it. The approach employed is a survey, including both secondary and primary data acquired from a variety of sources. This research use stratified random sampling and gini ratio analysis to achieve its objective. Using stratified sampling, responses from fishermen were collected. The income from fishing for motorized and non-powered boats in the Medan Belawan subdistrict was somewhat unequal, according to the study's findings. The moderate inequality indication in the group of fishermen who use boats with outboard motors can develop for a number of causes, including those listed below : The employment of more modern fishing equipment enables them to sail to more expansive fishing grounds/areas. Consequently, their catch rates are often substantially greater than those of non-motorized boat fishermen. There is a potential that if the Gini Ratio Index is computed for merging with groups of fishermen who have superior fishing means, then the Gini Ratio Index calculation results will be greater (income distribution is more unequal). The catch per trip of motorized boat fishermen in the Medan Belawan District has a beneficial impact on revenue. The catch has a substantial beneficial influence on the revenue of motorboat fisherman over the course of a year.; While it is negatively influenced by the expense of traveling to sea, the time spent going to sea, and the season, it is positively affected by the amount of fish caught. Positive influences on the revenue of motorbike-riding fisherman are the catch and the cost of traveling to sea, whereas negative influences are the number of employees, the time spent, and the season.